Metagenomics analysis of bacterial community structure from wood- and soil-feeding termites: metabolic pathways and functional structures toward the degradation of lignocellulose and recalcitrant compounds - Xie, Rongrong; Danso, Blessing; Sun, Jianzhong; Al-Tohamy, Rania; Khalil, Maha A.; Schagerl, Michael; Ali, Sameh S. (Frontiers in Microbiology, 2024)
Some essential information on gut bacterial profiles and their unique contributions to food digestion in wood-feeding termites (WFT) and soil-feeding termites (SFT) is still inadequate. The feeding type of termites is hypothesized to influence their gut bacterial composition and its functionality in degrading lignocellulose or other organic chemicals. This could potentially provide alternative approaches for the degradation of some recalcitrant environmental chemicals. Therefore, metagenomic analysis can be employed to examine the composition and functional profiles of gut bacterial symbionts in WFT and SFT. Based on the metagenomic analysis of the 16S rRNA gene sequences of gut bacterial symbionts in the WFT, Microcerotermes sp., and the SFT, Pericapritermes nitobei, the findings revealed a total of 26 major bacterial phyla, with 18 phyla commonly represented in both termites, albeit in varying abundances. Spirochaetes dominated the bacterial symbionts in Microcerotermes sp. at 55%, followed by Fibrobacters, while Firmicutes dominated the gut bacteria symbionts in P. nitobei at 95%, with Actinobacteria coming in second at 2%. Furthermore, the Shannon and phylogenetic tree diversity indices, as well as the observed operational taxonomic units and Chao 1 richness indices, were all found to be higher in the WFT than in the SFT deduced from the alpha diversity analysis. Based on the principal coordinate analysis, exhibited a significant distance dissimilarity between the gut bacterial symbionts. The results showed that the gut bacterial composition differed significantly between the WFT and SFT. Furthermore, Tax4Fun analysis evaluated bacterial functions, revealing the predominance of carbohydrate metabolism, followed by amino acid metabolism and energy metabolism in both Microcerotermes sp. and P. nitobei termites. The results implicated that bacterial symbionts inhabiting the guts of both termites were actively involved in the degradation of lignocellulose and other recalcitrant compounds.